2021
DOI: 10.3390/molecules26164854
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Antioxidant Capacity, Prebiotic Activity and Anticancer Potential in Human Cells of Jackfruit (Artocarpus heterophyllus) Seed Flour

Abstract: The general aim of this study was to evaluate physicochemical properties, prebiotic activity and anticancer potential of jackfruit (Artocarpus heterophyllus) seed flour. The drying processes of jackfruit seeds were performed at 50, 60 and 70 °C in order to choose the optimal temperature for obtaining the flour based on drying time, polyphenol content and antioxidant capacity. The experimental values of the moisture ratio during jackfruit seed drying at different temperatures were obtained using Page’s equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…nutritional value. They could be used as a component of functional foods because it is a rich source of phytonutrients (lignan, isoflavones, and saponins) and potential prebiotic effects [6,[7][8][9]. According to these findings, jackfruit seeds offer good nutritional content; antioxidant and prebiotic activities; and potential protective effects and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…nutritional value. They could be used as a component of functional foods because it is a rich source of phytonutrients (lignan, isoflavones, and saponins) and potential prebiotic effects [6,[7][8][9]. According to these findings, jackfruit seeds offer good nutritional content; antioxidant and prebiotic activities; and potential protective effects and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Sebelum dilakukan konseling, ibu hamil memberikan penilaian yang salah terhadap perilaku ibu hamil yang harus menghindari konsumsi buah nangka dan ubi jalar karena kedua makanan tersebut mengandung gas yang membuat ibu hamil menjadi tidak nyaman dan menjadi penyebab keguguran berulang pada ibu hamil muda. Buah nangka (Jackfruit/ Artocarpus Heterophyllus) memiliki kandungan nutrisi yang baik untuk ibu hamil seperti mencegah dan mengatasi sembelit, mengendalikan tekanan darah karena buah nangka memiliki kandungan kalium dan antioksidan yang baik, mengurangi keluhan kram kaki saat hamil (Trejo Rodríguez et al, 2021) (Sonpal, 2020).…”
Section: Kajian Pustakaunclassified
“…With a rich composition of phytochemicals such as flavonoids, phenolic compounds, and saponins, A. heterophyllus exhibits a wide range of biological activities, including antioxidant, antiinflammatory, antimicrobial, and anticancer properties [14][15][16][17]. One of the most intriguing aspects of A. heterophyllus is its custom of consuming green unripe jackfruit as a meal, an efficient alternative to rice for regulating blood sugar levels, owing to its soluble fiber, pectin content, and lower glycemic load [18]. Many studies have shown that bioactive components present in both unripe and ripened jackfruit help in mitigating diabetes and obesity-associated metabolic dysfunctions [16,19].…”
Section: Introductionmentioning
confidence: 99%